1995
DOI: 10.4315/0362-028x-58.11.1234
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatographic Analysis of Cellular Fatty Acids in the Identification of Foodborne Bacteria

Abstract: The cellular fatty acid composition of about 160 strains of Bacillus, lactic acid bacteria, Enterobacteriaceae, and Staphylococcus was analyzed in order to identify foodborne bacteria. In a first step, the reproducibility of the procedure, from the bacterial growth to the extraction and analysis conditions, was evaluated. The stability of fatty acid composition under controlled conditions was confirmed through high similarity levels (So ≥ 94). Secondly, intraspecies similarity was estimated. The existence of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…For many years, FA analysis has been recognized as a useful and rapid tool for the characterization of microorganisms in foods (1,2) and as a complementary analysis to taxonomic classification (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In addition, knowledge of the FA composition may help to evaluate the nutritional quality of alternative microbiological sources of fats (9,(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…For many years, FA analysis has been recognized as a useful and rapid tool for the characterization of microorganisms in foods (1,2) and as a complementary analysis to taxonomic classification (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In addition, knowledge of the FA composition may help to evaluate the nutritional quality of alternative microbiological sources of fats (9,(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Wauthoz et al [57] used GC analysis of cellular fatty acids for the characterization of foodborne bacteria and reported that fatty acid composition usually did not appear unique to a single species itself, so this method should only be used to complement other methods. Yeung et al [60] reported that FAME analysis using the microbial identification system (MIDI) led to very high variability among replicates.…”
Section: Discussionmentioning
confidence: 98%
“…In this study B. subtilis and B. licheniformis were allocated in the same group. WAUTHOZ et al (1995) analyzed cellular fatty acids of 160 strains of foodborne bacteria Bacillus (lactic acid bacteria, Enterobacteriaceae and Staphylococcus) and the best results of discrimination between species was obtained for the heterogeneous genus Bacillus, for which 12 species (23 strains) could be separated into 6 clusters at a 79% similarity level. In this work, B. licheniformis, B. pumilus and B. subtilis strains were grouped in the same cluster.…”
Section: Discussionmentioning
confidence: 99%